The Association Between Anterior Cruciate Ligament Length and Femoral Epicondylar Width Measured on Preoperative Magnetic Resonance Imaging or Radiograph - Reinette Van Zyl, B.Sc., M.Sc; Albert-Neels Van Schoor, B.Sc., M.Sc., Ph.D; Peet J. Du Toit, B.Sc., M.Sc., Ph.D; Farhana E. Suleman, M.B.Ch.B., F.C.Rad. Diag, M.Med. Rad.D; Mark D. Velleman, MB.Ch.B., F.C.Rad. Diag, M.Med.D; Vaida Glatt, Ph.D; Kevin Tetsworth, M.D., F.R.A.C.S; Erik Hohmann, M.B.B.S., F.R.C.S., F.R.C.S. (Tr&Orth) (Elsevier, 2020)
Purpose: To determine whether femoral epicondylar width (FECW) obtained from either magnetic resonance imaging (MRI) or plain radiographs could be used to predict anterior cruciate ligament (ACL) length. A secondary purpose was to develop a formula to use maximum FECW on either MRI or plain radiographs to estimate ACL length preoperatively. Methods: The MRIs and radiographs of 40 patients (mean age 41.0 years), with no apparent knee pathology, surgery, or trauma were included. The ACL length was measured on MRI followed by FECW on both MRI and radiograph of the same patient. This allowed the development of equations able to predict ACL length according to the FECW measured on either an MRI or radiograph. Results: The mean ACL length was 40.6 ± 3.6 mm. FECW measured on both MRIs and radiographs was sufficient to predict ACL length. Pearson's correlations revealed a high positive relationship between ACL length and FECW on MRI (r = 0.89, P < .0001) and ACL length and FECW on radiograph (r = 0.83, P < .0001). The coefficient of determination (R2) was calculated to be MRI: R2 = 0.78 and radiograph: R2 = 0.68 and confirmed that FECW measured on both MRI and radiograph were sufficient to predict ACL length. Based on these models, ACL length can be predicted by FECW using the following formulas: MRI: ACL length = 0.47 (FECW) + 1.93 and radiograph: ACL length = 0.31 (FECW) + 11.33. Conclusions: This study demonstrated that FECW measured on either MRI or anteroposterior radiograph could reliably estimate ACL length on a sagittal MRI. There was a high positive relationship between ACL length and FECW on both MRI and radiographs, although MRIs do predict ACL length more reliably. Clinical Relevance: Preoperative ACL length assessment, using FECW on MRI or radiograph, is useful in graft selection and in preventing inadequate graft harvesting for ACL reconstruction, especially if an individualized anatomical approach is pursued.